2010
DOI: 10.1104/pp.110.161661
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Profiling of Laser-Captured Pollen Mother Cells Indicates Molecular Pathways and Gene Subfamilies Involved in Rice Meiosis    

Abstract: Pollen mother cells (PMCs) represent a critical early stage in plant sexual reproduction in which the stage is set for male gamete formation. Understanding the global molecular genetics of this early meiotic stage has so far been limited to whole stamen or floret transcriptome studies, but since PMCs are a discrete population of cells in developmental synchrony, they provide the potential for precise transcriptome analysis and for enhancing our understanding of the transition to meiosis. As a step toward ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 69 publications
(69 reference statements)
4
108
0
Order By: Relevance
“…It is possible that, in contrast with the early GA biosynthesis genes, one or more GA20ox genes is expressed in pollen prior to meiosis and rescues mutant pollen development by migration of protein and/or mRNA into the subsequent microspores, as was suggested for components of the GA-signaling pathway in rice (Chhun et al, 2007). Indeed, on the basis of microarray data, Tang et al (2010) found expression of rice GA20ox1 and GA20ox3 in PMCs, while Hirano et al (2008) showed rice GA20ox4 expression in pollen at meiosis. Although comparable transcript analyses are not available for A. thaliana, we see weak GUS expression in PMCs for GA20ox1 and GA20ox2 ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that, in contrast with the early GA biosynthesis genes, one or more GA20ox genes is expressed in pollen prior to meiosis and rescues mutant pollen development by migration of protein and/or mRNA into the subsequent microspores, as was suggested for components of the GA-signaling pathway in rice (Chhun et al, 2007). Indeed, on the basis of microarray data, Tang et al (2010) found expression of rice GA20ox1 and GA20ox3 in PMCs, while Hirano et al (2008) showed rice GA20ox4 expression in pollen at meiosis. Although comparable transcript analyses are not available for A. thaliana, we see weak GUS expression in PMCs for GA20ox1 and GA20ox2 ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…It used to be technically challenging to isolate meiotic cells at a specific stage for RNA-seq analysis. Bright-field microscopy, 4',6-diamidino-2-phenylindole (DAPI) fluorescence staining, and laser capture of individual cells have made it possible to dissect these cells (Fujita et al, 2010;Tang et al, 2010;Yang et al, 2011). Using DAPI fluorescence staining and WE-CLSM techniques, we were able to obtain PMCs at precise stages of meiosis and identify genes that were differentially expressed during these stages in rice (Feng et al, 2001;Lu et al, 2002;Zhang et al, 2005Zhang et al, , 2006He et al, 2011aHe et al, , 2011bWu et al, 2014).…”
Section: Polyploidy Enhanced Epistatic Interactions Between Pollen Stmentioning
confidence: 99%
“…The complexity of gene expression during anther and ovary development has been revealed using microarrays or RNA sequencing in diploid rice (Tang et al, 2010;Aya et al, 2011;Deveshwar et al, 2011;Jin et al, 2013;Pan et al, 2014), maize (Zea mays; DukowicSchulze et al, 2014), wheat (Triticum aestivum; Crismani et al, 2006), and Arabidopsis (Arabidopsis thaliana; Twell, 2003, 2004;Yang et al, 2011;Zhao et al, 2014). Microarrays have been used to identify differentially expressed genes in autotetraploid plants.…”
mentioning
confidence: 99%
“…To clarify it, we examined the gene expression profile data of stamen meiotic cells generated in Tang's and Matsuoka's labs. Their data clearly revealed that OsTGA10 is detected in meiotic cells in rice stamen (Hobo et al, 2008;Tang et al, 2010).…”
Section: Ostga10 Is Preferentially Expressed During Stamen Developmentmentioning
confidence: 99%